Writing and Adapting Medicine-Related Texts for People with Autism Using "Social Stories" аnd "Easy Language" Methods - A.S. Kolganova; A.V. Obuhova (Moscow State University of Psychology and Education, 2023)
Currently, much attention is being paid to creating an accessible environment for various groups of people such as people with disabilities, the elderly, children and people for whom Russian is not native language. One of the most im- portant areas is adaptation of information materials on various topics. Providing accessible information about medical services can make medical visits much easier for a wide range of people, including those with autism spectrum dis- orders (ASD), who have difficulty understanding textual information due to mental, sensory, and other disabilities. Due to the fact that people with ASD do not always understand verbal information (both spoken and written), text materials for them need to be adapted. One of the methods to make text easier to understand is “Easy Language”. This method includes rules for creating and adapting textual and graphic information, making them accessible to a wide range of readers who have difficulties in understanding information. Another method developed to improve social skills and understanding of social situations in people with autism is “Social Stories”. This method combines techniques of visual support of textual materials. Social stories are short stories on a particular topic (most often accompanied by illustrations). Their main goal is to inform readers about characteristics of a specific phenomenon or situation, as well as about the ways of behavior in this situation. The article presents the experience of combining “Social Stories” and “Easy Language” methods as part of work to adapt informational medical texts for people with autism spectrum disorders. The work was carried out by specialists of the Moscow Center for Psychology and Educa- tion. Individual excerpts of social stories are used as an example to illustrate some rules of “Easy language” method.